Jerusalem : excavating 3000 years of history - Kenyon, Kathleen Mary (New York : McGraw-Hill, 1967)
Based on the results of an expedition sponsored by the British School of Archeology in Jerusalem, the Dominican ecole biblique et archeologique de St. Etienne, and the Royal Ontario Museum.
Bibliography: p. 202-203
Keywords: Jerusalem - Antiquities